Assessment of the Effect of Stone Quarrying on the Environment of Anguwa Uku Area, Gombe Metropolis, Gombe State - Yerima Bello, Mohammed; Muhammed Bashir, Bello; Ahmed, Abdulrazak; Mahdi Doho, Faiza; Abubakar, Abdulmajid; Sydney Uchenna, Okorocha; Yakubu Aliyu, Ibrahim (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
A significant direct and indirect predictor of human health is environmental quality. A significant factor in bad health and a miserable existence, declining environmental conditions also impede sustainable growth. This study aimed to assess the effects of stone quarrying on the environment and inhabitant of Anguwa Uku of Gombe Metropolis. In order to achieve the study aim, a mix-method research design was used, in which both quantitative and qualitative data were gathered. In-depth interviews (IDIs) and questionnaires were utilised to gather data for this investigation. For the purpose of gathering data, the participants and houses were chosen using purposive and systematic sampling techniques The quantitative and qualitative data was analysed using descriptive statistics. On the other hand, a theme method was used to analyse qualitative data. According to the data analysis results, 30.7% of the sampled respondents in the study area utilised a mechanical way of granite stone extraction, whereas 69.3% of them employed a manual method. In the study area, certified firms often utilise the mechanical approach, whereas self-employed miners mostly use the manual method. The majority of the miners in the research region, according to the results, utilised hammers (41.1%), dynamite (20.5%), diggers (12.8%), burning tires (10.2%), wagon drill (7.7%), and chisels (7.7%), to remove granite stone. However, the IDI's findings revealed that the local residents suffer greatly from the operations surrounding the quarrying site, including structural destruction, air and noise pollution, soil erosion, land degradation, pit creation, and flora destruction. In addition, the majority of residents’ experience chronic coughing, chest pain, breathing difficulties, vision issues, and hearing disorders. It was concluded that the study's local environment is damaged by quarrying operations; as a result, action must be taken to stop the situation in order to ensure sustainability in the future. The study recommends that companies should implement land reclamation measures at specific intervals to prevent flooding, land degradation, erosion, the creation of potentially dangerous pits, and other environmental issues that could negatively impact the study area's residents.